Kontribusi Variabel Makro Ekonomi (Studi Tentang Determinan Pertumbuhan Ekonomi di Indonesia 2010-2020). - Soleman, Riky; Wau , Taosige; Lestari, Aulia (Jurnal Ekonomika dan Bisnis Islam, 2023)
This study uses a panel data analysis method in the form of a cross-section of 34 provinces in Indonesia with a time-series from 2010-2020. Followed by using quantitative method analysis with the Eviews 10 analysis tool. The results of the model specification test state that FEM (Fixed Effect Model) is the best choice model to use. It is known that from all the independent variables, only some have a positive influence on economic growth, such as PMDN, the number of poor people, and the consumer price index (CPI) having a positive direction. This positive influence is caused by education, health and increased investment so that it can encourage economic growth. Inflation has a principle which states that not everything has a negative impact on the economy. Such as mild inflation that can provide the realization of economic growth. However, the variables TPAK, RLS, AHH and Islamic Banking Financing have a negative direction on Indonesia's economic growth. So, in the context of increasing economic growth, it can be concluded that the presence of several indicators such as a quality and productive workforce, equitable education and health, socialization of sharia banking to the community is more conducive so that economic growth in Indonesia is increasing.